Combined PCR-oligonucleotide ligation assay for rapid detection of Salmonella serovars. - Stone, G G (1995)
We have developed a rapid and sensitive assay for the detection of Salmonella serovars in veterinary clinical specimens. This method utilizes a short cultivation period followed by PCR. For detection of the amplified product, an enzyme-linked immunosorbent assay (ELISA)-based oligonucleotide ligation assay (OLA) was used. In this study, the PCR-OLA technique was compared with conventional culture and membrane hybridization for the detection of Salmonella bacteria. In evaluating the PCR-OLA with Salmonella serovars and non-Salmonella strains of bacteria, A490 readings for 51 Salmonella strains, representing 28 serovars, were significantly higher (P < 0.05) than those for 25 non-Salmonella bacteria. With serial 10-fold dilutions of Salmonella CFU or with known concentrations of purified chromosomal DNA from Salmonella typhimurium ATCC 29946, the PCR-OLA was able to detect > or = 20 CFU per assay or > or = 80 fg of chromosomal DNA (corresponding to 160 molecules of DNA). Of 102 suspect clinical specimens screened, 15 were positive for Salmonella bacteria by both culture and the PCR-OLA procedure (100% sensitivity), and 3 samples were positive only by PCR-OLA (96.6% specificity), indicating a positive predictive value of 83.3% and a negative predictive value of 100%. In all experiments, the PCR-OLA was as sensitive as membrane hybridization. These results indicate that a limited enrichment cultivation and PCR-OLA could be used as a presumptive screening test for the detection of Salmonella serovars from any sample that currently requires extensive cultivation and that this assay would be adaptable to automation.